Pemanfaatan Limbah FABA (Fly Ash Bottom Ash) dalam Penataan Ruang Komunal Anak di Kampung Nelayan Barombong Kota Makassar - Andi Asmuliany; Amalia, Andi Annisa; Irma Rahayu (Universitas Muhammadiyah Surakarta, 2023)
Communal space for children of Biringkassi Barombong fishing village is located in the outer space of residential buildings, namely in the transition zone between land, water and mangrove vegetation. Activities carried out by fishermen children include exploring, playing, increasing sensory to the playground, interacting, expressing and creating. However, some spaces in quality are not yet representative as play spaces. For this reason, it is necessary to arrange materials made from FABA waste that apply environmentally friendly principles. The aspect of efficiency because its use requires lower costs, local material categories, and is resistant to sea water and is very suitable for soil and water conditions in Barombong Fisherman Village. The purpose of national integrated research-based community service activities is to organize the communal space of fishermen's children by applying FABA Waste. The ABCD method is an asset-based community with FABA material as the main element in the arrangement because the material properties are environmentally friendly, easy to modify, and resistant to coastal environmental conditions with an area of 21 m2 can minimize coal waste from burning electricity. The socio-cultural activity space is located in the settlement transition area. The space is set as a children's play space in the natural and built space of the fishermen group. The distribution of these spaces includes ponds, soccer fields, bridges, backyards, and sandbars. The results of service activities in the form of ideas, designs and applications for utilizing FABA (Fly Ash and Bottom Ash) by building children's playgrounds can become prototypes while improving the quality of built environment assets, especially in urban coastal informal settlements.